„Moja podróż z językiem obcym” – narracyjne badanie autobiograficzne - Werbińska, Dorota (Neofilolog, 2010)
The aim of this article is to show some possibilities of using autobiographical narratives in the learning and teaching languages. The first part, focused on theoretical aspects of autobiographical research, points to its functions, problems for the researcher and possible content to be examined. The second part describes an example of the author’s autobiographical narrative research study conducted among the students of philological (English philology) and non-philological (elementary education with English and management) fields of study, whose task was to write an autobiography entitled "My journey with a foreign language".